Novel OCDMA Detection Technique based on Modified Double Weight Code for Optical Access Network - Ahmed, N.; Aljunid, S. A.; Ahmad, R. B.; Fadil, Hilal. A.; Rashid, M. A. (Elektronika ir Elektrotechnika, 2012)
In this paper a new detection technique known as NAND subtraction scheme based on Modified Double Weight (MDW) code for spectral-amplitude coding OCDMA (SAC-OCDMA) is proposed. The MDW code is the modified version of double weight (DW) code family. The theoretical and simulation results show that the new detection technique can have more better BER performance than other conventional techniques such as the AND and Complimentary subtraction techniques. The system performance was characterized by the signal to noise ratio (SNR), bit error rate (BER), and different Psr (-10 dBm). This study also shows that the new detection scheme can be achieved when the number of users are high and maintain the standard acceptable BER value ((≤10-9). DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2638